Pengembangan Sistem Manajemen Persediaan Bahan Baku berbasis Web (Studi Kasus: RM. Lalapan Ala Dewi) - Timoti Agape Siahaan; Tri Astoto Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Lalapan Ala Dewi Restaurant inventory management still uses conventional notes and reports. The number of branches and the need for raw ingredients of each branch becomes a weakness for the conventional way when managing the supply of raw ingredients. Such weaknesses affect the performance of each branch because it often runs out of raw ingredient supplies. A web-based raw ingredient inventory management system is needed to help with the problem. The raw ingredient inventory management system will record the raw ingredient inventory and report of each branch. The system is designed with a waterfall model method and uses an object-oriented approach. After the system was developed, the system was tested with white-box testing techniques and black-box testing techniques. The result of this research was raw ingredient inventory management system.